Simulating the Entire Clinical Process for an Implant‐Supported Fixed Prosthesis: In Vitro Study on the Vertical Implications of Implant‐Abutment Connections and Rotational Freedom - Holger Zipprich; Stefanie Ecker; Pauline Gutmann; Kathrin Seidel; Paul Weigl; Markus Schlee; Silvia Brandt (Wiley, 2024)
ABSTRACT Objectives The aim of this in vitro study was to investigate whether and to what extent different scenarios of rotational freedom in different IAC designs affect the vertical dimension of a three‐part fixed partial denture (FPD). At the same time, the experimental setup should simulate all clinical and laboratory steps of the implementation of such an FPD as accurately as possible. Material and Methods Twenty identical pairs of jaw models were fabricated from aluminum, each lower‐jaw model holding two implants with conical or flat IACs. Three impressions of each model were taken to fabricate stone casts and three‐unit FPDs. Three assembly scenarios were compared for the vertical position stability they offered for these FPDs, differing by how the sequential implant components (impression posts > laboratory analogs > abutments 1 > abutments 2) were aligned with the positional index of the IAC. In this way, a total of 60 stone casts and FPDs were fabricated and statistically analyzed for changes in vertical dimension (p < 0.05). Results Regardless of whether a conical/flat IAC was used (p > 0.05), significantly greater mean changes in vertical dimension were consistently (all comparisons p < 0.0001) found in a "worst‐case scenario" of component alignment alternating between the left‐ and right‐limit stop of the positional index (0.286/0.350 mm) than in a "random scenario" of 10 dentists and 10 technicians with varying levels of experience freely selecting the alignment (0.003/0.014 mm) or in a "best‐case scenario" of all components being aligned with the right‐limit stop (−0.019/0.005 mm). Conclusions The likelihood of integrating a superstructure correctly in terms of vertical dimension appears to vary considerably more with assembly strategies than with IAC designs. Specifically, our findings warrant a recommendation that all implant components should be aligned with the right‐limit stop of the positioning index.